A comparison of auditory and visual distraction effects: behavioral and event-related indices - Berti, Stefan; Schröger, Erich (Brain research. Cognitive brain research, 2001)
Infrequent task-irrelevant deviations in the frequency of a tone may distract our attention away from the processing of task-relevant tone duration. The distraction obtained in the auditory paradigm is reflected in prolonged reaction times in duration discrimination and in P3a. The P3a is followed by a late negative component, which may be related to a re-orienting process following distraction (RON, re-orienting negativity). The present study aimed at comparing effects of the auditory and a corresponding visual distraction paradigm. Distraction elicited a deviance-related negativity which revealed a modality-specific distribution. It was followed by P3a (350-ms post-stimulus) and by RON (500-ms post-stimulus). RON did not occur with long-duration visual stimuli indicating a difference in visual and auditory distraction. Moreover, the results suggest that in both tasks irrelevant deviants were detected by modality-specific processes which caused an attention shift.